Mantra dalam Kesusastraan Minangkabau dan Puisi-Puisi Sutardji Calzoum Bachri: Suatu Analisis Sastra Bandingan - Zulfadhli Zulfadhli (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2009)
This paper reveals a comparisons between magic spells / charms as one of Minangkabau spoken Literature and the poetries of Sutardji Calzoum Bachri. The theory of comparative literature is used to reveal the comparison. Thus, the aspects compared are the structure and Moslem’s religious values found in Minangkabau’s magic spells with Sutardji Calzoum Bachri’s poetries. In fact, both magic spells of Minangkabau spoken Literature and the poetries of Sturdji Calzoum Bachri’s have many things in common. First, structurally both genres contains similar element of sound, diction and language style. Through the analyses of diction and theme it is found that both the Minangkabau magic spells and the poems of Sutardji Calzoum reflects the Moslem’s value and ideology. Keywords: magic spells, poetry, comperative litearature.